The role of coastal biodiversity conservation on sustainability and environmental awareness in mangrove ecosystem of southern Malang, Indonesia - Zainal Abidin; Budi Setiawan; Abdul Wahib Muhaimin; Agustina Shinta (Society for Indonesian Biodiversity, 2021)
Abstract. Abidin Z, Setiawan B, Muhaimin AW, Shinta A. 2021. The role of coastal biodiversity conservation on sustainability and environmental awareness in mangrove ecosystem of southern Malang, Indonesia. Biodiversitas 22: 648-658. Southern coast of Malang, East Java, Indonesia has several mangrove ecosystems used for ecotourism, such as Clungup Mangrove Conservation Tiga Warna (CMC Tiga Warna). This area has consistently implemented ecotourism principles. Previously, it was assumed to be vulnerable from the damage due to differences in environmental awareness of ecotourists and local communities. This study aims to (i) describe the strategy of coastal biodiversity conservation to enhance environmental awareness and its sustainability; (ii) analyze the role of conservation on sustainability and environmental awareness, with sustainability as a mediating variable between conservation and environmental awareness. Data analysis was conducted with descriptive and Warp Partial Least Square (WarpPLS). The results indicate that empirical facts of conservation, sustainability, and environmental awareness in CMC Tiga Warna are relevant to the result of statistical analysis. Conservation is believed to form the environmental awareness of ecotourists and local communities and to maintain the sustainability of ecotourism destinations. In addition, the sustainability of ecotourism destinations serves as an effective mediator between conservation and environmental awareness, along with the modeling of environmental awareness enhancement in conservation-based coastal ecotourism. The proposed model explains that sustainability and environmental awareness variances are 23% and 25%, respectively. In summary, Destination Marketing and Management Organization of CMC Tiga Warna ecotourism is believed to improve environmental awareness of ecotourist and local communities by strengthening coastal biodiversity conservation programs in ecotourism areas and in maintaining sustainability.